Problem winy i odpowiedzialności za zbrodnię w Orestesie Eurypidesa - Czerwińska, Jadwiga (Collectanea Philologica, 2023)
The myth of Orestes provides an excellent opportunity to trace the issue of guilt, and thus responsibility for the crime of matricide. This theme was taken up in their dramas by all three greatest Greek tragedians: Aeschylus, Sophocles and Euripides. The subject of consideration in the article will be Euripides’ Orestes and the way the poet highlights the relationship between the personal motivation of the play’s protagonist and the divine command. The main issue will be an attempt to answer the question whether the protagonist’s actions in Euripides’ play were autonomous in nature or caused by divine determinism. Apart from Orestes, the analysis will be supplemented by commentaries by scholastics and their way of explaining and interpreting the issues outlined in the article.